Impact of Pregnancy History and 17-Hydroxyprogesterone Caproate on Cervical Cytokines and Matrix Metalloproteinases - Caritis, Steve N.; Hankins, Gary; Hebert, Mary; Haas, David M.; Ahmed, Mahmoud; Simhan, Hyagriv; Haneline, Laura A.; Harris, John; Chang, Justine; Famy, Alyssa Stephenson; Yorio, Patrick; Ren, Zhaoxia; D'Alton, Mary E.; Venkataramanan, Raman (American Journal of Perinatology, 2018)
Objective The objective of this study was to evaluate the impact of pregnancy history and 17-hydroxyprogesterone caproate (17-OHPC) treatment on cervical fluid cytokines and matrix metalloproteinases (MMPs).Study Design Cervical fluid was obtained between 160/7 and 246/7 weeks from women with only prior term births (controls, n = 26), women with one or more prior spontaneous preterm births (SPTBs) choosing to receive 17-OHPC (17-OHPC, n = 24), or to not receive 17-OHPC (refusers, n = 12). Cervical fluid collections were repeated 2, 4, and 8 weeks after the first sample and concentrations of MMPs and cytokines were measured by multiplex immune assay.Results Among women whose earliest prior delivery occurred between 16 and 23 weeks, cervical fluid concentration of interleukin (IL)-6, IL-10, and tumor necrosis factor (TNF)-α at baseline were significantly elevated when compared with cervical cytokines of women whose earliest delivery occurred between 32 and 36 weeks (relative risk ratio was 3.37 for IL-6 [95% confidence interval, CI, 1.08–10.53, p < 0.05], 2.81 for IL-10 [95% CI, 1.39–5.70, p < 0.05], and 6.34 for TNF-α [95% CI, 2.19–18.68, p < 0.001]). Treatment with 17-OHPC had no significant impact on these cytokines.Conclusion The cervical fluid of women with a history of an early prior SPTB is characterized by inflammation that is unaffected by 17-OHPC.
Keywords: 17-hydroxyprogesterone caproate; cytokines; matrix metalloproteinases; cervicovaginal; inflammatory milieu